CO2 Sequestration, Biofuels and Depollution - Lichtfouse, Eric; Schwarzbauer, Jan; Robert, Didier (Environmental Chemistry for a Sustainable World, 2015)
Water is the driving force of all nature. This old quote from Leonardo da Vinci remind us that without water life is simply not possible. As a consequence, water is probably the most important wealth for humanity. In spite of this, drinking water is still polluted by man-made toxicals gathered by waters in soils and the atmosphere. This book presents advanced methods to clean water and air. Chapters also focus on biofuels, greenhouse gases and genetically modified crops.